FRAKSINASI DAN IDENTIFIKASI SENYAWA TANIN PADA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Elok Kamilah Hayati; A. Ghanaim Fasyah; Lailis Sa’adah (Jurnal Kimia (Journal of Chemistry), 2010)
Fractionation of tannic compound from star fruit leaves was conducted by maseration using acetone : water(7:3), and analytical and preparative thin layer chromatography using a variety of eluents. The isolates obtained wereidentified using UV-Vis and FT-IR Spectrophotometer.The best eluent for both analytical and preparative TLC was found to be n-butanol : water : acetic acid(4:1:5), which gave three isolates with Rf of 0.53, 0.61, and 0.68. The second isolate (Rf = 0.61), showed a maximumabsorption at 331 nm on the UV-Vis spectra. Its IR spectra showed specific absorptions such as OH-assymetricstretch (3372.2 cm-1), aromatic overtone (2071.8 cm-1), and aromatic and benzene stretches at 1625.8 cm-1 and 782.5cm-1 respectively. These spectra suggest that the tannic compound was either flavan pent-3,6,7,4',5'-ol or flavanpent-3,7,8,4',5'-ol.